Chronic rhinosinusitis on radiological examination: literature review - Anshor Nugroho; Puspita Anggraini Katili; Siti Fauziyah Rahman (International Journal of Health Science and Technology, 2022)
Rhinosinusitis is a manifestation of the presence of inflammation in the nasal cavity and mucous membrane of the paranasal sinuses resulting in the formation of fluid or damage to the bone structures below. Radiological support examination in cases of rhinosinusitis can be done with conventional X-ray radiology examination of the paranasal sinuses, which can be combined with computed tomography (CT) or Magnetic Resonance Imaging (MRI) radiology examination. This study compares traditional imaging, CT scanning, and MRI in patients with chronic rhinosinusitis. A comprehensive literature review was employed in the study to locate, analyze and interpreting all information pertaining to chronic rhinosinusitis cases. The maxillaris, frontalis, ethmoidalis, and sphenoidalis sinuses with processus alveolar and petrous ridge can be seen without superposition on conventional x-rays. The complete paranasal sine and its surrounding anatomy can be seen with a CT scan, which has the best sensitivity and can show a difference in slice thickness of just 1 mm.  MRI examination can clearly distinguish between soft tissue and body fat and is used to support therapy in cases of rhinosinusitis and does not cause radiation.